Improvement of Strength of soft Clay Soil by Using cement kiln dust, fly ash and Ceramic Dust waste (Times New Roman Bold 12) - Ghaidaa Kadhim Abd, Abdul Aziz Abdul Rasoul (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Soft clay soils have relatively low strength and high compressibility. For this reason, the construction of the subgrade in soft clay soils has encountered many difficulties. Expensive solutions are utilized in some engineering projects, which usually involve removing and replacing soft soils. Instead, land improvement is currently the best solution to such problems. this paper aim to decrease the use of Portland cement and lime as the most common stabilizers utilized for soft soils, use recycled waste materials and demolition and construction waste as an alternative to stabilize soft clay soils at south of Iraq. was use waste materials such as fly ash (FA), cement kiln dust (CKD) and Marble dust wastes (MDW) to improve soft clay soils in south of Iraq. Some standard laboratory geotechnical tests were conducted to examine some changes in the engineering properties of treated soils with waste cement kiln dust (CKD), fly ash (FA) or ceramic dust waste (CDW) with proportions of (5%,10%,15%) by dry weight of soil. Laboratory tests performed on treated and untreated soil samples included standard compaction tests, Atterberg limits tests, and California Bearing Ratio (CBR) tests. The results showed that FA-soft clay soil samples and CKD-soft clay soil samples showed a decrease in liquid limits (LL%) and plasticity index (P.I%) and the increase in the plastic limits (P.L%) in addition to an increase in the maximum dry density (MMD) and a decrease in the optimum moisture content (OMC%) and an increase in the immersed and non-immersed (CBR) values. While the results of CDW-soft clay soil samples showed a decrease in liquid limits (L.L%), plastic limit (P.L%), the optimum moisture content (OMC%), plasticity index (P.I%) In addition to showed an increase in the maximum dry density (MDD) and an increase in the immersed and non-immersed CBR values. The data that emerged from the testing programs showed that (FA), (CKD) or (CDW) can be utilized to improve soft clay soil, but there is a certain percentage of using them in the improvement, as the best percentag e of (FA) was at (10%) by dry weight of soil and the best percentage for (CKD) and (CDW) they were at (15%) by dry weight of soil, but (CKD) stabilizer show much more improvement than (CDW) and (FA), while (CDW) shows greater improvement compared to (FA). In general, these stabilizers can be utilized to improve the geotechnical properties of soil.